2014
DOI: 10.1111/1469-0691.12555
|View full text |Cite
|
Sign up to set email alerts
|

Steps towards the discovery of Mycobacterium tuberculosis by Robert Koch, 1882

Abstract: Palaeomicrobiology has detected the tuberculosis agent in animal and human skeletons that are thousands of years old. The German doctor Robert Koch was the first microbiologist to report in 1882 the successful isolation of the causative agent of tuberculosis, named 1 year later as Mycobacterium tuberculosis. This immense discovery, however, was not made from scratch, but involved the combining of previous scientific knowledge, chiefly the previous demonstration by the French doctor Jean-Antoine Villemin that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 31 publications
0
85
0
5
Order By: Relevance
“…Harz observed structures similar to reproductive bodies and hyphae of fungi; therefore, he considered the microorganism to be a fungus and named it Actinomyces bovis [14]. In 1882, Robert Koch discovered another microorganism during his observations using light microscopy that is now recognized as an actinobacterium: the tuberculosis pathogen Mycobacterium tuberculosis [16]. Koch observed that the microbes presented morphological characteristics that were similar to those of microorganisms previously described by Hansen associated with leprosy disease [17].…”
Section: Historical and Taxonomic Aspectsmentioning
confidence: 93%
“…Harz observed structures similar to reproductive bodies and hyphae of fungi; therefore, he considered the microorganism to be a fungus and named it Actinomyces bovis [14]. In 1882, Robert Koch discovered another microorganism during his observations using light microscopy that is now recognized as an actinobacterium: the tuberculosis pathogen Mycobacterium tuberculosis [16]. Koch observed that the microbes presented morphological characteristics that were similar to those of microorganisms previously described by Hansen associated with leprosy disease [17].…”
Section: Historical and Taxonomic Aspectsmentioning
confidence: 93%
“…One hundred thirty-five years after Robert Koch's discovery, Mycobacterium tuberculosis remains a major cause of mortality, with two million deaths attributed to tuberculosis (TB) annually (Cambau and Drancourt, 2014;Padhi et al, 2014). TB control has been hampered by the emergence of M. tuberculosis strains refractory to standard treatment regimens.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that Robert Koch reported the isolation of M. tuberculosis in Ͻ10 days by inoculating a simple serum-based medium has been neglected (10). With the MOD9 culture medium, we resurrected the Koch's serum-based medium from the late 19th century, adding growth enhancers to propose a protocol that is now routinely used at La Timone Hospital for the rapid detection of tuberculosis and nontuberculous mycobacteria.…”
Section: Discussionmentioning
confidence: 99%